2002
DOI: 10.1016/s0014-5793(02)02628-5
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein W is a glutathione‐dependent antioxidant in vivo

Abstract: The function of selenoprotein W (Se-W) was investigated by cloning the corresponding cDNA from mouse brain and expressing it in CHO cells and H1299 human lung cancer cells. Overexpression of Se-W markedly reduced the sensitivity of both cell lines to H 2 O 2 cytotoxicity. The intracellular peroxide concentration of the transfected cells was lower than that of the parental cells in the absence or presence of extracellular H 2 O 2 . The resistance to oxidative stress conferred by Se-W was dependent on glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 22 publications
5
89
0
Order By: Relevance
“…100 The analogy with the motif Cys-X-X-Cys of Trx, high affinity for GSH, and overexpression against oxidative stress in muscle tissues suggest an antioxidant function. 101 However, the precise molecular pathways are not yet elucidated, so the specific functions remain unknown.…”
Section: Selenoproteins S and Kmentioning
confidence: 99%
See 1 more Smart Citation
“…100 The analogy with the motif Cys-X-X-Cys of Trx, high affinity for GSH, and overexpression against oxidative stress in muscle tissues suggest an antioxidant function. 101 However, the precise molecular pathways are not yet elucidated, so the specific functions remain unknown.…”
Section: Selenoproteins S and Kmentioning
confidence: 99%
“…101 The SeCys residues 13 and 37 have been shown to be necessary for the antioxidant activity of SelW, which is downregulated by GSH, but seem to be not correlated with intracellular levels of reactive oxygen species (ROS). SelW was also found to be a specific molecular target of methylmercury in human neuronal cells, whereas other Se-proteins were not affected.…”
Section: Selenoproteins S and Kmentioning
confidence: 99%
“…However, CpSelW in length of amino acid was the same as chicken one and was shorter than rodent one (Whanger, 2009;Ou et al, 2011). Selenocysteine 13 or cysteine 37 was replaced by serine and did not render cells resistant to hydrogen peroxide (Jeong et al, 2002). All selenocysteine 13 were conserved, residue number 37 was cysteine in mammalian SelW, but fish, chicken and CpSelW contained threonine, arginine, and serine, respectively.…”
Section: Danio Rerio (Np_840072)mentioning
confidence: 97%
“…Litopenaeus vannamei SelM expression was transiently induced in gills after infection with the white spot syndrome virus (WSSV) on a time dependent manner (Clavero-Salas et al, 2007), the expression of selenoprotein glutathione peroxidase mRNA was significantly and could be induced by pathogen challenge (De Zoysa et al, 2008;Yeh et al, 2009;Liu et al, 2010). It was suggested that SelW was an antioxidant protein for lipid peroxidation (Jeong et al, 2002;Whanger, 2009). However, the expression of CpSelW was different during A. hydrophila infection between hepatopancreas and hemocytes of mussels.…”
Section: Danio Rerio (Np_840072)mentioning
confidence: 99%
See 1 more Smart Citation